2021
DOI: 10.3390/fi13020043
|View full text |Cite
|
Sign up to set email alerts
|

Digital Communication Tools and Knowledge Creation Processes for Enriched Intellectual Outcome—Experience of Short-Term E-Learning Courses during Pandemic

Abstract: Social isolation during the pandemic contributed to the transition of educational processes to e-learning. A short-term e-marketing education program for a variety of students was introduced in May 2020 and is taught entirely online. A survey was conducted regularly in the last week of training using Google Forms, and three cohorts were surveyed in July, September, and December 2020. A high level of satisfaction indicates an interest in the content and a positive assessment of the level of comfort of an organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…A study conducted at Universidad del Valle de México confirmed teachers' ability to assimilate quickly in the Ms Teams environment [48]. Satisfaction with a range of digital communication tools used for elearning was demonstrated in a study conducted among students in St. Petersburg in 2020 [49].…”
Section: Literature Reviewmentioning
confidence: 89%
“…A study conducted at Universidad del Valle de México confirmed teachers' ability to assimilate quickly in the Ms Teams environment [48]. Satisfaction with a range of digital communication tools used for elearning was demonstrated in a study conducted among students in St. Petersburg in 2020 [49].…”
Section: Literature Reviewmentioning
confidence: 89%
“…Unfortunately, it did not involve Indonesia, which has various population characteristics and unequal digital literacy. In another case, Pokrovskaia et al also identified the e-learning implementation in Russia during the COVID-19 pandemic using three hypotheses [10] which its results focused on hypotheses testing only. Those studies utilized a quantitative approach only so the respondents were limited in expressing their perception when evaluating the online classes.…”
Section: Introductionmentioning
confidence: 99%
“…Faced with the new situation of online teaching, brought about by COVID-19, teaching has been forced to seek and create new forms and spaces that allow future teachers to develop them effectively. Several authors have pointed out the difficulty and complexity of creating spaces that enable the development of these transversal competences online [41,42]. However, authors such as [43,44] proposed a new paradigm that links learning theories with technological tools based on a sociocultural vision of cognition that advocates that learning processes are essentially social in nature and are nourished by technology in terms of the potential it offers for creating, enriching or favouring interpersonal learning contexts, which they call computer-supported collaborative learning (CSCL).…”
Section: Discussionmentioning
confidence: 99%